2022
DOI: 10.3389/fneur.2021.781482
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Rehabilitation Telehealth During the SAEA-CoV-2 (COVID-19) Pandemic

Abstract: During the COVID-19 pandemic, physical therapists transitioned to provide telehealth in the United States. We sought to determine the experiences of physical therapists delivering telerehabilitation for vestibular disorders including barriers, preferences, and concerns. A survey was created using the results of a focus group and previously published studies. The survey was distributed across social media sites and through email- the link was sent to the orthopedic, neurologic, and geriatric academies of the Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Individuals with other common diagnoses (including amyotrophic lateral sclerosis, spinal cord injuries, traumatic brain injuries, and vestibular disorders) report great satisfaction and engagement over telehealth, but there is a dearth of quantitative evidence demonstrating improvements in motor function. 8,[36][37][38] In contrast, providers lack confidence in the accuracy of a virtual diagnosis and share patient safety concerns when using telehealth. 38 Findings From Mobile Applications.…”
Section: Objective 1: To Bridge the Knowledge Gap By Evaluating The C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with other common diagnoses (including amyotrophic lateral sclerosis, spinal cord injuries, traumatic brain injuries, and vestibular disorders) report great satisfaction and engagement over telehealth, but there is a dearth of quantitative evidence demonstrating improvements in motor function. 8,[36][37][38] In contrast, providers lack confidence in the accuracy of a virtual diagnosis and share patient safety concerns when using telehealth. 38 Findings From Mobile Applications.…”
Section: Objective 1: To Bridge the Knowledge Gap By Evaluating The C...mentioning
confidence: 99%
“…8,[36][37][38] In contrast, providers lack confidence in the accuracy of a virtual diagnosis and share patient safety concerns when using telehealth. 38 Findings From Mobile Applications. Due to the exponential growth in the number of commercially available PT, rehabilitation, and wellness smartphone applications "apps" (ie, software programs downloaded by a user on a mobile app) and limited information on the use and quality of these apps, it is a significant challenge to utilize or recommend them in a health care setting.…”
Section: Objective 1: To Bridge the Knowledge Gap By Evaluating The C...mentioning
confidence: 99%
“…It is therefore anticipated that digital health will be embedded in future care, will solve the problems of access, and allow a greater understanding of exercise parameters. In a recent VR specific survey, 80% of therapists agreed that telehealth was an effective mode of delivering treatment but reported challenges with providing the written exercise programme and concerns about testing balance remotely with no caregiver present ( 8 ), and in a large survey of US physical therapists, 40% reported using telehealth software for the first time in 2020 ( 9 ). A benefit of the pandemic has been the requirement to use technology for daily human interactions beyond health care, and this has likely increased acceptance and familiarity with remote interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, therapists face many considerations when transitioning to digital care, and barriers are often cited as cost, IT infrastructure, data privacy and security, and uncertainty around efficacy ( 10 , 11 ). Also, amongst therapists and patients, there remains a preference for face-to-face care, in a profession that is known for its “hands-on” approach ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Due to the limited access to medical care provider during the COVID-19 pandemic, telemedicine for diagnosis and treatment of BPPV was proposed as a good alternative. [18][19][20] To our knowledge, this study is the first to examine the impact of COVID-19 on the incidence of BPPV subtypes by hospital visit (OPD vs ER), and the mean time interval between vertigo onset and primary evaluation. Our data demonstrated that the total number of BPPV patients who were diagnosed in the ER and OPD decreased by 15.9% (517 to 435) during the…”
mentioning
confidence: 99%